Platelet-Rich Plasma (PRP) in Hair Restoration Treatments: A Comprehensive Review of Existing Literature - Cyran, Piotr; Jaroszyńska, Anna; Jaroszyński, Filip; Kowal, Joanna; Paleczny, Jan; Parobczak, Robert; Połujański, Paweł; Winciorek, Joanna; Wiśniewska, Adrianna (Journal of Education, Health and Sport, 2024)
Hair loss is a common concern affecting individuals worldwide. With various therapies available to address this issue, it prompts the search for effective treatments and prevention methods. Platelet-Rich Plasma (PRP) therapy has emerged as a promising option for hair restoration, leveraging the regenerative properties of platelets to stimulate hair growth. This comprehensive review aims to synthesize the existing literature on the use of PRP in hair restoration treatments. A systematic search of major databases was conducted to identify relevant studies evaluating the efficacy and safety of PRP therapy for hair loss of the scalp. Eligible studies were selected based on predetermined inclusion criteria, and data extraction was performed to capture key findings, including patient demographics, PRP preparation methods, treatment protocols, and outcomes measured. The review encompasses both clinical trials and observational studies, providing insights into the effectiveness of PRP therapy in promoting hair regrowth, improving hair density and therefore enhancing patient satisfaction. Additionally, safety considerations, adverse events, and limitations of current evidence are discussed. Overall, this review highlights the growing body of evidence supporting the use of PRP in hair restoration treatments while identifying areas for further research and clinical refinement.